2017
DOI: 10.1212/wnl.0000000000003550
|View full text |Cite
|
Sign up to set email alerts
|

Refractory status epilepticus in children with and without prior epilepsy or status epilepticus

Abstract: Objective: To compare refractory convulsive status epilepticus (rSE) management and outcome in children with and without a prior diagnosis of epilepsy and with and without a history of status epilepticus (SE).Methods: This was a prospective observational descriptive study performed from June 2011 to May 2016 on pediatric patients (1 month-21 years of age) with rSE.Results: We enrolled 189 participants (53% male) with a median (25th-75th percentile) age of 4.2 (1.3-9.6) years. Eighty-nine (47%) patients had a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
(30 reference statements)
2
30
0
Order By: Relevance
“…Our results remained robust to the alternative comparison of periods 2011 to 2016 and 2017 to 2019 when the evidence for delays was even stronger. 24 Our results were also robust when considering only the hospitals that formed pSERG initially. Our main results remained robust to these sensitivity analyses and together show no major improvements in time to treatment within pSERG after publication of evidence of delays in time to treatment.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our results remained robust to the alternative comparison of periods 2011 to 2016 and 2017 to 2019 when the evidence for delays was even stronger. 24 Our results were also robust when considering only the hospitals that formed pSERG initially. Our main results remained robust to these sensitivity analyses and together show no major improvements in time to treatment within pSERG after publication of evidence of delays in time to treatment.…”
Section: Discussionsupporting
confidence: 51%
“…As more patients were collected, new pSERG analyses in 2016 confirmed the initial results and showed that delays in time to treatment of rSE were common even in patients with a prior diagnosis of epilepsy. 24 Further, the American Epilepsy Society evidence-based guideline Glossary ASM = antiseizure medication; BZD = benzodiazepine; CI = confidence interval; HR = hazard ratio; ICU = intensive care unit; OR = odds ratio; p25 = 25th percentile; p75 = 75th percentile; pSERG = Pediatric Status Epilepticus Research Group; RMST = restricted mean survival time; rSE = refractory convulsive SE; SE = status epilepticus. published in 2016 emphasized initial treatment with BZD within 20 minutes, treatment with non-BZD ASM within 40 minutes, and treatment with continuous infusions within 60 minutes.…”
Section: Variablesmentioning
confidence: 99%
“…Five out of the 22 studies have used the operational definition of SE to include >5 min of seizure activity [33]. Two studies used >15 min [25,26], two studies used failure of >2 antiepileptic drugs [11,32,34], one used the inclusion criteria of witnessed seizures and receiving at least one anticonvulsant [29] and another used the chief complaint of seizure in emergency department as the inclusion criteria [20]. Thirteen paediatric studies [1,[9][10][11]13,14,22,[24][25][26]29,30,32], eight adult studies [2,4,15,20,23,27,28,31], and one study with both paediatric and adult populations [21] were included ( Table 1).…”
Section: Characteristics Of the Target Population And Studiesmentioning
confidence: 99%
“…The acute seizure CPG recommend prompt administration of first‐line BZD at 5 min with a repeat dose at 10 min and escalation to second‐line therapy by 20 min. CPGs recommend such an approach because there is evidence to show better seizure control with earlier AED administration . Repeated administration of first‐line agents like BZD can delay the institution of more definitive therapy.…”
Section: Discussionmentioning
confidence: 78%
“…CPGs recommend such an approach because there is evidence to show better seizure control with earlier AED administration. 19 Repeated administration of first-line agents like BZD can delay the institution of more definitive therapy. After the first few minutes, there is internalisation of GABA receptors through which BZD acts, and BZD will not be effective.…”
Section: First-line Treatmentmentioning
confidence: 99%